Konsep Ri’ayah dalam Hadis Kepemimpinan: Studi Terhadap Kepemimpinan Kepala Sekolah - Andi Sitti Emeralda Ria; Ismail, La Ode; Sakka, Abdul Rahman (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2025)
This study investigates the concept of ri’ayah in Prophetic traditions on leadership and its applicability to the leadership practices of school principals within the education sector. Employing a descriptive qualitative approach and thematic analysis of selected traditions, the research identifies five key components of ri’ayah: managerial responsibility, collaboration, adaptability, religiosity, and justice. The findings demonstrate that incorporating these principles significantly enhances the effectiveness of school leadership, particularly in optimizing resource management, cultivating an inclusive and harmonious learning environment, and advancing the development of students and educators. Moreover, the study underscores the intersection between ri’ayah and servant leadership, which prioritizes service-oriented values, compassion, and integrity as pivotal to achieving educational excellence. By bridging Islamic teachings and contemporary leadership theories, this article contributes to academic discourse while offering practical insights for school principals to foster high-quality, competitive, and ethically grounded educational environments.